Biomedical and health sciences publication productivity from Malaysia - Zainal, Hazmir; Zainab, Awang Ngah (Wiley, 2011)
Background: The aim of this study was to examine Malaysian contributions in the field of biomedical and health sciences. Methods: In this study, 3697 publications affiliated to Malaysian addresses from the sci database between 1990 and 2005 were sampled. This study also explored publication productivity trends, authorship and collaboration pattern, core journals used, and citations obtained. Results: Main contributions were journal articles (73.3%). Most authors (63.7%) contributed only one article and 16.1% produced over 30-68 publications. Multi-authored works were the norm. The productive authors were named either first or second in publications. There were active collaborations with authors from Asia-Pacific countries (35%) and Europe (30%). The majority of publications were contributed by institutions of higher learning (87%). Core journals used follow quite close to Bradford's zonal ratios of 44:152:581. The active research areas were identified. About 71.3% of publications received citations especially those published from 1995 to 1999. Conclusion: This study helped librarians identify active researchers, active research areas and journals relevant to biomedical and health sciences researchers and useful when producing reports to university management and planning medical collection policies and deciding on journal subscriptions and cancellations. © 2011 The authors. Health Information and Libraries Journal © 2011 Health Libraries Group.